The effect of microstructure on the oxidation and carburisation of 9Cr-1Mo steel exposed to CO2. (October 2021) - Coghlan, L.; Yan, S.; Shin, A.; Pearson, J.; Jepson, M.A.E.; Higginson, R.L.
Graphical abstract: Highlights: Substrate carbide distribution is dictated by the substrate microstructure. Formation of carbides leads to elemental segregation, dependant on microstructure. Martensitic 9Cr-1Mo shows greater carburisation relative to ferritic 9Cr-1Mo steel. Preferential oxidation of Cr leads to the formation of the internal oxidation zone. Shadows of the prior microstructure are present in the oxide due to Cr segregation. Abstract: To understand the effect of microstructure on the oxidation characteristics of 9Cr-1Mo steel, experimental material with two different starting microstructures (ferritic and martensitic) were exposed to a CO2 rich atmosphere at 600 °C and 640 °C for up to ∼7000 h. The microstructure influences the size and distribution of carbides forming within the 9Cr-1Mo steel exposed to a CO2 rich atmosphere. These differences lead to elemental segregation during carburisation and oxidation. This elemental segregation influences the oxidation characteristics of the 9Cr-1Mo steel and the morphology of the internal oxidation zone, and subsequently the spinel structure shows ghosts of the prior substrate microstructure.